(untitled) (International Journal of Biology and Chemistry, 2018)
Development of simple, fast and accurate methods for quantification of volatile organic compounds (VOCs) in soil samples is important for providing greater efficiency of analytical laboratories in Kazakhstan and other developing countries. Naphthalene is a model polycyclic aromatic hydrocarbon (PAH), belonging to a group of compounds of significant concern due to environmental impact. Solid-phase microextraction (SPME) is an optimal method for solvent-free automated sample preparation for determination of VOCs in environmental samples. In this work, the method for quantification of naphthalene in soil based on headspace SPME, gas chromatography with mass spectrometric detection, and standard addition calibration was developed. The parameters of SPME and sample equilibration after spiking with standards were optimized for better control of the soil matrix effect. The SPME temperature 80 °C provided the greatest accuracy of naphthalene responses for soils with different matrix and humidity. Equilibration of soil samples after spiking with standards for 6 h at 80 °C provided stabilization of responses in soils with different matrix and water content. The greatest accuracy and precision were achieved after equilibration of the samples for 8 h. The method provides recoveries of 105-119% in the concentration range 0.01-0.1 ng g-1 with detection limit 0.001 ng g-1. The developed method was applied for quantification of naphthalene in real soil samples collected in Almaty, Kazakhstan. The measured concentration of naphthalene in real soil samples varied in the range of 1.4 to 47 ng g-1. In five out of ten collected soil samples concentration exceeded a maximum permissible concentration of 15 ng g-1.